The Evolution of the Fed Batch Ethoxylation Reactors to Produce the Non-Ionic Surfactants - Di Serio, Martino; Russo, Vincenzo; Santacesaria, Elio; Tesser, Riccardo (Frontiers in Chemical Engineering, 2021)
The most recent reactor technology to produce non-ionic surfactants via ethoxylation reaction is illustrated in the present work. The most advanced reactors are deeply illustrated for what concerns the working principle and the main performance. In detail, Venturi Loop Reactor (VLR), Spray Tower Loop Reactor (STLR) and Enhanced Loop Reactor (ELR) are depicted, and the related performance compared. ELR shows the highest flexibility, to reach the desired ethoxylation degree, and at the same time good performances comparable with the VLR. Moreover, ELR allows to reach high ethoxylation degree, as in this condition, a good mixing, in the case of high liquid expansion, is difficult to be achieved with the other reactors. Thus, it is possible to work at higher ethoxylation degree respecting safety issues. Finally, a comprehensive model was proposed to describe quantitatively the mentioned reactors. The model is characterized by a general validity and can be easily adapted to each specific reactor configuration.